Control of graphene nanoplatelets at the interface of the co-continuous polypropylene/polyamides 6 blend under the elongational flow. (3rd January 2023) - Chen, Jianming; Zhang, Jingjing; Deng, Jingyi; Qiu, Shaohong; Zheng, Jiahui; Chen, Yunan; Zhang, Weiqi; Huang, Shijun; Chen, Anfu; Lei, Caihong
Graphical abstract: Highlights: The introduction of elongational flow enlarges the volume ratio range of the formation of co-continuous structure. The graphene nanoplatelets are oriented along the phase interface and remain at the interface steadily. The conductivity of composites prepared under the elongational flow improve significantly compare with shear flow. Abstract: Controlling the filler selective distribution at the interface of co-continuous polymer blend is an effective way to fabricate high performance composites. In this work, the graphene nanoplatelets (GNPs) were distributed at the interface of co-continuous polypropylene (PP)/polyamides 6(PA6) blend by melt blending under the elongational flow generated by convergent-divergent channels. And the formation of co-continuous structure and migration mechanism of GNPs in the PP/PA6 blend under the elongational flow were discussed based on the analysis of rheological measurement, scanning electron micrographs, selective etching experiment and thermal conductivity measurement. The results show that both PP and PA6 phase are elongated into fibrous phase structure under the elongational flow. This indeed enlarge the volume ratio range of composites forming co-continuous structure. And GNPs are oriented along the phase interface and stay at the interface during migration under the elongational flow, which can improve its in-plane thermal conductivity. The in-plane thermal conductivity of the PP/PA6/GNPs composites prepared under the elongational flow are all higher than those prepared under the shear flow. Particularly, the composite prepared under the elongational flow with the 65/35 vol ratio of PP/PA6 still kept a co-continuous structure and the GNPs distributed at the interface. Its in-plane thermal conductivity reached a maximum value of 1.13 W/m K.